Nowsze problemy teoretyczne pisania o sobie. Przykład wypowiedzi autobiograficznych pisarzy polskich ostatnich dziesięcioleci - Lubas-Bartoszyńska, Regina (Wydawnictwo Naukowe UAM, 2006)
The newer theoretical problems in the autobiography of Polish writers have been presented on theoretical and analytical planes. Among other theoretical issues one can find the problem of integrity, equating autobiography with novel and generally with fiction and separatism which relies on these distinctions. The author takes the position in between the issues but at the same time perceives a strong tendency "to write about oneself", which results in the appriopriation of the field by fiction and essay. Hence the limitation in divisions of broadly understood autobiography to: "simple" autobiography and autobiography of men of letters; the classical and modern; reference and literary, those written in the form of a journal and reminiscent writing (autobiography in the narrow sense and memoirs). The analysis of autobiographic texts of the recent years have been limited to selected newer problems, such as: the issue of the Other, "unreality of the past", journal as a current experience. The issue of auto fiction and blog has also been commented on.
Newer theoretical problems in writing about oneself: An example of autobiographical writings by Polish writers of the recent decades